Central administrations of hemopressin and related peptides inhibit gastrointestinal motility in mice. Issue 6 (14th March 2016) - Li, X.‐H.; Lin, M.‐L.; Wang, Z.‐L.; Wang, P.; Tang, H.‐H.; Lin, Y.‐Y.; Li, N.; Fang, Q.; Wang, R.
Abstract: Background: Hemopressin was identified as an endogenous inverse agonist/antagonist of CB1 receptor, whereas VD‐hemopressin( α ) [VD‐Hp α ] and VD‐hemopressin( β ) [VD‐Hp β ] were found as the novel endogenous peptidic agonists of cannabinoid receptors. As cannabinoids are potent modulators of gastrointestinal (GI) motility, our aim was to characterize the effects of hemopressin and related peptides on GI motility in vivo . Methods: The responses of intracerebroventricular (i.c.v.) administration of the reference compound WIN55, 212‐2, hemopressin, and related peptides to GI motility were investigated by measuring upper GI transit, colonic bead expulsion, and whole gut transit in mice. Key Results: Central administration of the classical cannabinoid receptor agonist WIN55, 212‐2 dose‐dependently slowed upper GI transit, colonic expulsion, and whole gut transit via CB1 receptor. Similarly, Hp α, VD‐Hp α, and VD‐Hp β delayed upper GI transit and colonic expulsion after i.c.v. administration. At the high doses, Hp α and VD‐Hp β inhibited whole gut transit, whereas VD‐Hp α had no effect on whole gut transit. In addition, the effects of these three peptides on GI transit were antagonized by the CB1 receptor selective antagonist AM251, but not by the CB2 receptor selective antagonist AM630. Conclusion & Inferences: The endogenous cannabinoid peptide ligands hemopressin, VD‐Hp α, and VD‐Hp β inhibited GI transit through the activation of CB1, but not CB2 cannabinoid receptors. The lower potencies of the hemopressin and related peptides in GI transit assays may be important for the future development of cannabinoid peptides as the therapeutic analgesics with limited GI side effects. Abstract : Our studies, for the first time, revealed that central administration of hemopressin and related peptides, the novel endogenous peptidic ligands of cannabinoid receptors, significantly inhibited gastrointestinal motility in mice through the activation of CB1, but not CB2 cannabinoid receptors.